INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) MELALUI PEMANFAATAN MEDIA PEMBELAJARAN KONTEKSTUAL DAN PENGEMBANGAN BUDAYA RELIGIUS DI SEKOLAH - Edi Nurhidin (Universitas Islam Lamongan, 2017)
Islamic education subject, as one of obligated subjects on every formal educational hierarchy in Indonesia, which is hoped can create every one has religious characteristic, is valued has not reach the decided goal. Here, the important Islamic education subject learning innovation which complete, integrated and appropriate with quick development of information and communication technology. This study, discusses about one of alternative solution of Islamic education subject learning by contextual media utilization and religious culture development. Islamic education subject is not enough learned only on the classroom because learning on the classroom more focus on student cognitive dimension. So, needed religious cultural. Brevity, the aim of learning process on the classroom by learning media utilization (technology/ non-technology) is to maximize knowledge and student comprehension about religious knowledge. While, the aim of religious climate on the school is to habituate and construct student applying their religious knowledge and comprehension, especially in pray, attitude and behavior on daily life.